Spatial disparity in the levels of Human Development in Himachal Pradesh - Aashish, Pankaj; Sharma, D.D. (National Geographical Journal of India, 2022)
The study assesses the pattern of disparity in human development in Himachal Pradesh for three census years 1991, 2001, and 2011, applying the human development index method based upon the combination of selected human development indicators. An attempt has also been made to compare the levels of human development among various blocks of the state. The human development index shows that states Southwestern region is far more and symmetrically developed in comparison of Central and North-eastern regions in three decades. The results show that wide disparities in the human development index exist among different blocks. The study suggests that less developed blocks require improvement in most of the indicators for enhancing their levels of overall human development.